Asset management within commercial banking groups - Ferreira, Miguel A. (2022)
Funfing agency: International Monetary Fund (IMF), University of Toronto, Villanova University, Fuel Cell Technologies Program, Texas A and M University, University of Hong Kong, Universiteit Maastricht, Georgia State University, McGill University, Howard University School of Business, Universiteit van Tilburg, European Research Council (ERC), Fundacao para a Ciencia e Tecnologia (FCT) and Richard A. Mayo Center for Asset Management at the Darden School of Business